Enabling thermal efficiency improvement and waste heat recovery using liquid air harnessed from offshore renewable energy sources. (1st October 2020) - Osorio, Julian D.; Panwar, Mayank; Rivera-Alvarez, Alejandro; Chryssostomidis, Chrys; Hovsapian, Rob; Mohanpurkar, Manish; Chanda, Sayonsom; Williams, Herbert
Highlights: A novel approach to harness offshore renewable energy sources is proposed. Cycle technical description from cryogen generation to end-use of energy is provided. Using liquid air improves thermal cycle efficiency and allows waste heat recovery. Liquid air favors indirect integration of renewable energy sources in the electric grid. A Round-Trip Efficiency of up to 70% is possible with the proposed decoupled system. Abstract: A novel approach using decoupled processes to harness offshore renewable energy, from marine hydrokinetics, ocean waves, wind, and solar to produce liquid air, is presented in this paper. Offshore renewables interconnection using submarine medium- and high-voltage direct current technologies are used to produce liquid air that can be transported to end-use locations using repurposed liquefied natural gas tankers. Two important possibilities arise from using the proposed technology. The first possibility allows the integration with conventional thermal cycles to improve efficiency. This approach can be used to leverage efficiencies of thermal systems that have already reached a plateau in the maximum achievable efficiency via design and operation optimization. The second possibility is related to the incorporation of low temperature cycles to recover waste heat from other thermal processes. This is important considering that waste heat accounts for more than 60% of the consumed energy in the United States. A detailed technical description of the complete cycle from cryogen generation to end-use of energy is provided. Estimation of efficiency enhancement for thermal plants using liquid air including waste heat recovery is presented.